The Intelligent kWh Export-Import Utilizing Classification Models for Efficiency in Hybrid PLTS - Muchlis Baso; Salama Manjang; Ansar Suyuti (Bright Publisher, 2024)
Electricity demand is integral to the stability of the community's economic condition, where currently electricity is predominantly sourced from fossil fuels, posing limitations. One effort to maintain this stability is through the utilization of renewable energy, particularly solar energy. The abundance of solar energy in Indonesia presents an opportunity to maximize its potential. This study develops an intelligent kWh export-import system based on the Internet of Things (IoT) and integrated with machine learning. Users can access real-time conditions via mobile based on three parameters: